The use of Liposuction to treat significant contour abnormalities associated with Lipomyeloeningocoele. Issue 8 (August 2022) - Digney, Clare; Martin, Serena; Shanmuganathan, Mano; Marjanovic, Josip; Hill, Chris
ABSTRACT: Introduction: Since 1972 when first pioneered, liposuction has developed and is now one of the commonest aesthetic procedures performed worldwide. Evidence of its application in aesthetic lipomodelling is widely known, but there are scant reports in the literature on the use of liposuction in more unusual cases. We report its use as a safe and successful method of contour correction in two cases of lipomyelomeningocoele (LMMC), a form of spina bifida. To our knowledge, this has never been reported before. Method: A prospective review was performed and both cases were followed up during the treatment period. Both patients were treated at the Royal Belfast Hospital for Sick Children. Patient charts were reviewed and magnetic resonance imaging was used. Results: Two patients, aged 11 and 17 years, had a large LMMC over the lumbosacral area. Preoperative imaging was obtained in each case to ensure the procedure could safely avoid the underlying spinal cord structures. The use of the Microaire© suction device allowed precise fat extraction. Postoperative images demonstrate reduction of lipomatous bulk and improved contour. Conclusion: We have shown that when used with caution liposuction is a safe and effective technique for volume reduction of a LMMC in carefully selected cases.